A Retrospective Analysis of Systemic Bartonella henselae Infection in Children - Ramona Florina Stroescu; Flavia Chisavu; Ruxandra Maria Steflea; Gabriela Doros; Teofana-Otilia Bizerea-Moga; Dan Dumitru Vulcanescu; Teodora Daniela Marti; Casiana Boru; Cecilia Roberta Avram; Mihai Gafencu (Microorganisms, 2024)
Systemic Bartonella henselae infection, also known as cat-scratch disease (CSD), presents a diagnostic challenge due to the variability of clinical manifestations and the potential for serological cross-reactivity with other organisms. This study aimed to retrospectively analyze the epidemiological, clinical, laboratory, and imaging characteristics of pediatric patients diagnosed with systemic B. henselae infection, to improve understanding and facilitate timely diagnosis and treatment. We conducted a 10-year retrospective study at the “Louis Turcanu” Children’s Emergency Hospital and private clinics in Timisoara, Romania, reviewing records for confirmed cases of B. henselae infection from January 2014 to January 2024. The study adhered to the Declaration of Helsinki and received approval from the Institutional Review Board. Diagnostic criteria included contact with animals, prolonged fever, hematological and/or hepatosplenic manifestations, and positive serological tests for B. henselae. Nineteen pediatric patients were identified with a median age of 8.1 years. The majority were exposed to felines (94.7%), reflecting the disease’s epidemiological profile. Clinical findings highlighted fever (47.4%), lymphadenopathy (78.9%), and less frequently, abdominal pain and headache (both 10.5%). Laboratory analyses revealed a mean hemoglobin of 12.6 mg/dL, WBC count of 13.1 × 103 cells/microliter, and platelet count of 340.6 × 103 per microliter. Significant findings included elevation in ESR and CRP in 47.4% and 21.1% of patients, respectively, and high seropositivity rates for B. henselae IgM (63.2%) and IgG (94.7%). Imaging studies demonstrated widespread lymphadenopathy and occasional splenomegaly and hepatic microabscesses. All patients received antibiotic therapy, with azithromycin being the most commonly used (94.7%). Co-infections with Epstein–Barr Virus, Cytomegalovirus, and Toxoplasma gondii were documented, indicating the complex infectious status of the patients. Systemic B. henselae infection in children predominantly manifests with fever and lymphadenopathy, with a significant history of exposure to felines. Laboratory and imaging findings support the diagnosis, which is further complicated by potential co-infections. Effective antibiotic therapy, primarily with azithromycin, underscores the need for comprehensive diagnostic and treatment strategies. This study emphasizes the importance of considering systemic B. henselae infection in pediatric patients with prolonged fever and contact with cats, to ensure timely and appropriate treatment.